Collaborative Governance Model in Waste Reduction Efforts in Jombang Regency - Khoirrill, Oktavia Putri; Priambodo, Bayu (Department of Government Studies, Universitas Syiah Kuala, 2025)
The number of waste problems in Indonesia is still relatively high from year to year, including in Jombang Regency. The existence of this waste problem requires a response using a collaborative process between various parties/stakeholders from across sectors namely the government, private sector, and communities that have the authority or are called collaborative governance because each party cannot work alone. The purpose of this research is to analyze and describe waste reduction efforts in Jombang Regency. This research uses a descriptive qualitative research approach. This research focuses on collaborative governance in waste reduction efforts in Jombang Regency by using Ansell and Gash's theory with four indicators. This research focuses on collaborative governance in waste reduction efforts in Jombang Regency using Ansell and Gash's theory with four indicators, namely starting conditions, facilitative leadership, institutional design, and collaboration process. The data collection techniques used were interviews, observation, and documentation. The results showed that collaborative governance in the implementation of waste reduction efforts in Jombang Regency is already running well. However, in the collaboration process, the implementation has not been fully maximized because face-to-face dialogue does not occur regularly.